Experimental study on the effect of core flow heat transfer enhancement on the performance of TEG. (April 2022) - Li, Yanzhe; Wang, Shixue; Zhao, Yulong; Yue, Like
Abstract: Using thermoelectric power generation technology to recycle and utilize the waste heat of high temperature gas can effectively improve the efficiency of the energy. Filling foam metal (FM) at the core flow field of the thermoelectric generator (TEG) can effectively enhance the heat transfer of the TEG passage hot end and reduce the pressure loss, which can further optimize the power generation efficiency of TEG. Therefore, this article compares the effect of thermoelectric module with different performance on the power generation efficiency of TEG under the enhanced heat transfer mode of core flow filled with FM through experiments. The results showed that when the TEG passage hot end partially filled with FM at core flow field, the power output and power generation efficiency of the TEG can be significantly increased. And when high figure of merit (ZT) thermoelectric module is used in TEG, the overall performance of the TEG is also greatly improved.